Kôwelidē: An Inculturative Ecotheology A Study of Postcolonial Theology in the Death Rites of the Yei People in South Papua - Indonesia - Maximilian Boas Pegan; Avelinus Moat Simon; Godfridus Cindu Kosnan; Fransiskus Asisi Wanda Batlayeri (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2025)
Understanding and engaging with culture is essential for developing local theology. Every culture contains unique traditions and practices that embody noble values, some of which align closely with Christian teachings. Many cultural rituals hold deep significance for human life and reflect the community’s worldview, ethics, and spirituality. This article explores the noble values embedded in the local culture of the Yei people from South Papua, Indonesia, particularly in relation to their significant efforts to preserve the integrity of God’s creation. One crucial tradition, kôwelidē, is performed during death rites and incorporates practices aimed at environmental preservation. This study employs qualitative research methods, drawing on a postcolonial theology approach, to uncover the ecological wisdom of the Yei people. The research findings highlight a deep-rooted concept of environmental stewardship, which is then developed into a framework of inculturation of ecotheology. This approach integrates the lived experiences of the Yei people with theological reflections on nature conservation, emphasising a harmonious relationship between faith, culture, and environmental responsibility.